2018
DOI: 10.1039/c7nr07118c
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of polysulfides within bi-functional metal–organic frameworks for high performance lithium–sulfur batteries

Abstract: A lithium-sulfur (Li-S) battery is regarded as the most promising candidate for next generation energy storage systems, because of its high theoretical specific capacity (1675 mA h g) and specific energy (2500 W h kg), as well as the abundance, low cost and environmental benignity of sulfur. However, the soluble polysulfides LiS (4 ≤ x ≤ 8) produced during the discharge process can cause the so-called "shuttle effect" and lead to low coulombic efficiency and rapid capacity fading of the batteries, which seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 42 publications
0
65
0
Order By: Relevance
“…MOFs, known as porous coordination polymers (PCPs), are a kind of crystalline porous materials composed of metal ions/clusters nodes and organic ligands linkers in an infinite array configuration . By simply adjusting the metal species, geometry, size, and functionality of the modules, various kinds of MOFs could be realized, nowadays counting more than 20000 type of MOFs .…”
Section: Sulfur Cathodesmentioning
confidence: 99%
“…MOFs, known as porous coordination polymers (PCPs), are a kind of crystalline porous materials composed of metal ions/clusters nodes and organic ligands linkers in an infinite array configuration . By simply adjusting the metal species, geometry, size, and functionality of the modules, various kinds of MOFs could be realized, nowadays counting more than 20000 type of MOFs .…”
Section: Sulfur Cathodesmentioning
confidence: 99%
“…[28][29][30][31][32] For example, a Ni-based NiÀ MOF can effectively fix the polysulfide into the cathode structure with physical and chemical interactions synergistic effects, thereby enhancing the cycle performance of NiÀ MOF/S composite. [28][29][30][31][32] For example, a Ni-based NiÀ MOF can effectively fix the polysulfide into the cathode structure with physical and chemical interactions synergistic effects, thereby enhancing the cycle performance of NiÀ MOF/S composite.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs constructed by open metal sites (OMSs) and/or organic ligands with Lewis basic functional groups are promising host materials. 62,63,[110][111][112] Previous studies have shown that the coordinatively unsaturated OMSs in MOFs, such as HKUST-1, 111 Ni 6 (BTB) 4 (BP) 3 (BTB = benzene-1,3,5-tribenzoate and BP = 4,4 0 -bipyridyl), 62 MOF-525, 63 and Cu-TDPAT (H 6 TDPAT = 2,4,6-tris(3,5-dicarboxylphenylamino)-1,3,5-triazine), 112 can serve as Lewis acidic sites and provide chemical affinities to interact with sulfur and polysulfides. Based on the calculations by Siegel and Park, OMSs are revealed as the dominant adsorption sites for S 8 , Li 2 S 4 , and Li 2 S. 113 In the Li 2 S 4 chain, the sulfur atoms contact the OMSs, while the terminal lithium atoms tend to be adjacent to the organic moieties (e.g., oxygen anions or nitrogen groups in ligands).…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%
“…Based on the calculations by Siegel and Park, OMSs are revealed as the dominant adsorption sites for S 8 , Li 2 S 4 , and Li 2 S. 113 In the Li 2 S 4 chain, the sulfur atoms contact the OMSs, while the terminal lithium atoms tend to be adjacent to the organic moieties (e.g., oxygen anions or nitrogen groups in ligands). 112,113 Despite these improvements, the practical utilization of MOFs as sulfur host materials for LSBs is greatly restricted by their poor electrical conductivity, which leads to some severe issues, including slow redox kinetics and limited sulfur utilization, and, thus, a poor rate capability and cycling stability. Combining MOF/sulfur composites with conductive additives, such as carbon materials (e.g., reduced graphene oxide and carbon nanotubes) and polymers (e.g., polypyrrole and poly(3,4-ethylenedioxythiophene)), has shown some possibility in alleviating this issue.…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%